The relativity of regulatory T cell suppression modes - Bai, Lu; Choudhary, Vivek; Feng, Yongqiang (Frontiers in Immunology, 2026)
Foxp3-expressing CD4 regulatory T (Treg) cells are essential for maintaining immune tolerance through antigen-specific and bystander suppression modes. They carry a diverse T-cell antigen receptor (TCR) repertoire against a broad spectrum of antigens. The TCR repertoire acquired during Treg induction exhibits significant variations across antigens, leading to uncertainty in target coverage and representation. Accumulating reports indicate a remarkable complexity in the functional modes of Treg cells under various immunological contexts, presenting significant challenges for further investigation. In this article, we propose that the relative significance and capabilities of Treg suppression modes shift according to the levels of specific antigens and the resulting TCR signal strength. Testing the applicability of this model and identifying its modifiers would offer valuable insights for basic research and translational applications.